Anisotropic particles templated by Janus emulsion. Issue 35 (13th April 2015) - Ge, Lingling; Lu, Shuhui; Han, Jie; Guo, Rong
Abstract : Crescent-to-moon shaped anisotropic particles in both micrometer and nanometer size have been successfully fabricated in batch scale with Janus emulsion as template. Abstract : Anisotropic particles, with morphology from crescent to moon shape and size from micrometer to nanometer scale, are fabricated in batch scale with Janus emulsion as template. The strategy is also useful in the synthesis of Janus particles with chemically distinct hemispheres.